2019
DOI: 10.3847/1538-4357/ab48ea
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Mg ii during Solar Flares. II. Nonequilibrium Effects

Abstract: To extract the information that the Mg ii NUV spectra (observed by the Interface Region Imaging Spectrograph; IRIS), carries about the chromosphere during solar flares, and to validate models of energy transport via model-data comparison, forward modelling is required. The assumption of statistical equilibrium is typically used to obtain the atomic level populations from snapshots of flare atmospheres, due to computational necessity. However it is possible that relying on statistical equilibrium could lead to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 45 publications
1
22
0
Order By: Relevance
“…We use a 10-level-plus-continuum Mg II atom that is the same as in Leenaarts et al (2013a). Nevertheless, RH solves the radiative transfer equation under the assumption of statistical equilibrium instead of non-equilibrium ionization, which can change the ionization fraction and lead to a different line formation height (Kerr et al 2019c). In order to mitigate this effect, we adopt the values of the electron density and hydrogen density from RADYN that conform to the non-equilibrium ionization and fix them in RH calculations, as done in Rubio da Costa & Kleint (2017) and Kerr et al (2019b).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We use a 10-level-plus-continuum Mg II atom that is the same as in Leenaarts et al (2013a). Nevertheless, RH solves the radiative transfer equation under the assumption of statistical equilibrium instead of non-equilibrium ionization, which can change the ionization fraction and lead to a different line formation height (Kerr et al 2019c). In order to mitigate this effect, we adopt the values of the electron density and hydrogen density from RADYN that conform to the non-equilibrium ionization and fix them in RH calculations, as done in Rubio da Costa & Kleint (2017) and Kerr et al (2019b).…”
Section: Methodsmentioning
confidence: 99%
“…In order to mitigate this effect, we adopt the values of the electron density and hydrogen density from RADYN that conform to the non-equilibrium ionization and fix them in RH calculations, as done in Rubio da Costa & Kleint (2017) and Kerr et al (2019b). We do note that for those weaker flares in our simulations (the f9 and f10 models), there will be non-equilibrium effects in the main heating phase (Kerr et al 2019c). However, for strong flares, the difference in the Mg II resonance line profiles between statistical equilibrium and non-equilibrium ionization is smaller than the difference between PRD and CRD in the main heating phase (Kerr et al 2019c).…”
Section: Methodsmentioning
confidence: 99%
“…The methods used in this paper can easily be extended and applied to the analysis of smaller flares, which would greatly extend the statistical validity of these results. It would also be of interest to investigate whether these correlations vary between smaller and larger flares, since there may exist fundamental differences in ionization equilibrium timescales (Kerr et al 2019a). Additionally, the MINE network represents a highly versatile tool, which could also be used to examine the mutual information between two different data types, such as images and spectra.…”
Section: Discussionmentioning
confidence: 99%
“…Kerr et al (2019a) showed that PRD effects are still important even in the presence of increased collisional rates from enhanced densities. Furthermore, the assumption of statistical equilibrium appears to hold for strong flares (Kerr et al 2019b). The Mg II k-line also has a companion of triplets at 2791.60, 2798.75 and 2798.82 Å, with the two mixed subordinate lines in the red wing going into emission during flares.…”
Section: Spectral Linesmentioning
confidence: 98%